An annotated checklist and key to the Bulgarian cockroaches (Dictyoptera: Blattodea) - Hristov, Georgi H.; Chobanov, Dragan P. (Zootaxa, 2016)
An annotated checklist of the Bulgarian species of cockroaches is prepared based on a full published scientific record and own unpublished data. According to the current state of knowledge the Bulgarian cockroach fauna includes 17 species and subspecies. One synonymization is established—Phyllodromica marginata erythronota Br. v. W., syn. n. = Ph. marginata. Two species (Capraiellus tamaninii and Supella longipalpa) are recorded for the first time for this country and other three (Ectobius punctatissimus, Phyllodromica subaptera and Phyllodromica pallida) are eliminated from the list of the Bulgarian fauna. The list is complemented with maps and full locality data and a dichotomic identification key for the studied taxa is presented.